Development of early maladaptive schemes in teenage pregnancy of a residential care - Pérez, Lucía (2016)
The present article is based on our research work; its purpose was to find early maladaptive schemas developed by adolescent mothers living in a residential care. The sample consisted of  24 of these young people, aged among 13 and 19 years. The instrument applied was the Young Schema Questionnaire 3rd. Edition and a demographic form to obtain descriptive data on the  sample. When we obtained the results, we found that the predominant pattern in the sample was 50% abandonment. Other schemas were also observed such as emotional deprivation, mistrust and abuse, social isolation, dependency, vulnerability, subjugation, self-sacrifice, approval seeking, pessimism and emotional inhibition. Other result obtained which supports our hypothesis, was that most predominant patterns correspond to the dimension of disconnection and rejection in 41.7% of the sample. This indicates that the main need, which was not covered, was contact and secure attachment.